2013
DOI: 10.1111/ijfs.12296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postharvest storage conditions on the colour and freshness parameters of raw honey

Abstract: The influence of temperature (25, 30, 35 and 40°C) and storage time (up to 62 or 104 days) on colour; hydroxymethyl furfural (HMF) content; and diastase index (ID) of citrus, rosemary, eucalyptus, polyfloral and honeydew honey was evaluated. Decreases in luminosity, whiteness index, hue and chroma with the increase in temperature and storage time were observed to different extents depending on the botanical origin of the honey. At all temperatures, the highest values of chromatic parameters throughout the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
(38 reference statements)
2
18
0
2
Order By: Relevance
“…The low HMF content of the honeys in the present study was attributed to the fact that they were newly harvested honeys (not stored for a long duration), not treated with heat, and stored under proper conditions before sending for analysis. These results supported by Visquert et al [38] who found low HMF (<10 mg/kg) in all honey samples. Therefore, HMF should not be used for the identification of adulterated honey produced by overfeeding the honey bees with industrial commercial sugars.…”
Section: Discussonsupporting
confidence: 89%
“…The low HMF content of the honeys in the present study was attributed to the fact that they were newly harvested honeys (not stored for a long duration), not treated with heat, and stored under proper conditions before sending for analysis. These results supported by Visquert et al [38] who found low HMF (<10 mg/kg) in all honey samples. Therefore, HMF should not be used for the identification of adulterated honey produced by overfeeding the honey bees with industrial commercial sugars.…”
Section: Discussonsupporting
confidence: 89%
“…However, Kuroishi et al (2012) found a trend for the WI to increase in samples stored for 3 weeks at 11 and 21°C, as a result the formation of crystals in the honey. Contrary, Visquert et al (2014) stated the decrease of WI for citrus and rosemary honeys stored at 25°C for 104 days from 48.3 to 45.1 and from 33.7 to 30.2. As well, the decrease of WI after storage of honey at RT was observed in the present study.…”
Section: Colour Characteristicsmentioning
confidence: 92%
“…Other factors that would influence the kinetics of Maillard browning could be the type and thermal stability of amino acids and reducing sugars which participate in the reaction (Turkmen et al 2006). Visquert et al (2014) reported that citrus and rosemary honeys stored for 104 days at 25°C had total colour difference (DE) of 3.89 and 8.30, respectively while at 30°C approximately 16.01 and 9.51. Additionally, the decrease of a*, b* and C* values in frozen samples, could be linked to changes in the morphology of crystalline structure of analysed honeys.…”
Section: Colour Characteristicsmentioning
confidence: 99%
“…Retail samples reached values of up to 58 mm Pfund. These higher values could be mainly due to the influence of industrial thermal treatments (liquefaction and pasteurisation) (Visquert et al, 2014). Although colour level is not a requirement for citrus honey commercialisation, if this honey was sold with a specific quality mark, then particular colour requirements would have to be met.…”
Section: Validation Of Methyl Anthranilate Analytical Methodologymentioning
confidence: 99%